2004
DOI: 10.2337/diabetes.53.5.1285
|View full text |Cite
|
Sign up to set email alerts
|

From Blood Monocytes to Adipose Tissue-Resident Macrophages

Abstract: Obesity has been suggested to be a low-grade systemic inflammatory state, therefore we studied the interaction between human adipocytes and monocytes via adipose tissue (AT)-derived capillary endothelium. Cells composing the stroma-vascular fraction (SVF) of human ATs were characterized by fluorescence-activated cell sorter (FACS) analysis and two cell subsets (resident macrophages and endothelial cells [ECs]) were isolated using antibody-coupled microbeads. Media conditioned by mature adipocytes maintained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
398
3
19

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 545 publications
(450 citation statements)
references
References 31 publications
19
398
3
19
Order By: Relevance
“…This study revealed that the human ATM is characterized by high expression of MR, CD163 and integrin avb5. Moreover, the data support the model of obesity-associated macrophage infiltration of the AT 2,3,[26][27][28] by showing that the abundance of CD14 pos MR pos ATMs correlates with the BMI. As a secondary outcome of this study, human M2 macrophages were for the first time thoroughly analyzed regarding surface protein expression thus corroborating other studies mainly investigating gene expression and/or murine cells.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This study revealed that the human ATM is characterized by high expression of MR, CD163 and integrin avb5. Moreover, the data support the model of obesity-associated macrophage infiltration of the AT 2,3,[26][27][28] by showing that the abundance of CD14 pos MR pos ATMs correlates with the BMI. As a secondary outcome of this study, human M2 macrophages were for the first time thoroughly analyzed regarding surface protein expression thus corroborating other studies mainly investigating gene expression and/or murine cells.…”
Section: Discussionsupporting
confidence: 76%
“…27,31 So far, only CD31 and CD45 have been shown to be expressed on the surface of human CD14 pos cells derived from the AT. 26 However, CD45 is expressed on all haematopoietic cells and CD31 is expressed to a similar extent on ATMs and PBMs. Therefore, these markers do not reliably identify ATMs, particularly in preparations from visceral tissue that we found to be highly contaminated with PBMs, the abundance of which does not correlate with BMI (Figure 1b, Supplementary Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The attraction of monocytes to adipose tissue may be due to local production of monocyte chemoattractant protein-1 [13,29]. Adipocytes enhance chemotaxis and diapedesis of monocytes, via the regulation of endothelial cell adhesion molecules, promoting their infiltration into adipose tissue as macrophages [12].…”
Section: Discussionmentioning
confidence: 99%
“…It appears that macrophages and adipose cells may influence each other via paracrine mediators or direct cellular processes [11]. For example, diapedesis and the infiltration of monocytes and their differentiation into macrophages in adipose tissue were shown to be modulated by factors secreted by adipose cells [12,13]. Macrophages have also recently been implicated in scavenging dying adipocytes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Cells from the stroma vascular fraction were separated as described. 23 Adipose tissue-derived cells were homogenized in denaturing buffer from RNeasy kit (Qiagen, Courtaboeuf, France) and stored at À801C until RNA preparation. The local committee on ethics approved the project.…”
Section: Study Subjects and Clinical Examinationmentioning
confidence: 99%